How does firm diversification impact innovation?. Issue 4 (3rd April 2018) - Orlando, Beatrice; Renzi, Antonio; Sancetta, Giuseppe; Cucari, Nicola
ABSTRACT: This study sheds light on the relationship between business diversification and innovation. A diversification strategy is both a driver of sunk costs and strategic slack. Strategic slack is a valuable reserve of knowledge, usable to foster innovation. Using linear models, we explore the interplay between research and development (R&D) and organisational slack in large and diversified companies listed on the Euronext 100 Index. We consider the diversification pattern over time, and its interactions with the following three categories: sunk costs, slack resources, and R&D. The results show an antithetic effect of diversification and slack on R&D expenditures. In contrast to unabsorbed and potential slack, diversification and sunk costs hinder innovation. However, diversification is a huge source of strategic slack and, thus, has a positive effect on innovation, indirectly.